Luteolin delays photoreceptor degeneration in a mouse model of retinitis pigmentosa - Liu, Xiao-Bin; Liu, Feng; Liang, Yi-Yao; Yin, Gang; Zhang, Hui-Jun; Mi, Xue-Song; Zhang, Zai-Jun; So, Kwok-Fai; Li, Ang; Xu, Ying (Neural regeneration research, 2021)
Luteolin is neuroprotective for retinal ganglion cells and retinal pigment epithelial cells after oxidative injury, whereby it can inhibit microglial neurotoxicity. Therefore, luteolin holds the potential to be useful for treatment of retinal diseases. The purpose of this study was to investigate whether luteolin exhibits neuroprotective effects on rod cells in rd10 mice, a slow photoreceptor-degenerative model of retinitis pigmentosa. Luteolin (100 mg/kg) intraperitoneally injected daily from postnatal day 14 (P14) to P25 significantly enhanced the visual performance and retinal light responses of rd10 mice at P25. Moreover, it increased the survival of photoreceptors and improved retinal structure. Mechanistically, luteolin treatment attenuated increases in reactive oxygen species, photoreceptor apoptosis, and reactive gliosis; increased mRNA levels of anti-inflammatory cytokines while lowering that of pro-inflammatory and chemoattractant cytokines; and lowered the ratio of phospho-JNK/JNK. Application of the JNK inhibitor SP600125 exerted a similar protective effect to luteolin, suggesting that luteolin delays photoreceptor degeneration and functional deterioration in rd10 mice through regulation of retinal oxidation and inflammation by inhibiting the JNK pathway. Therefore, luteolin may be useful as a supplementary treatment for retinitis pigmentosa. This study was approved by the Qualified Ethics Committee of Jinan University, China (approval No. IACUC-20181217-02) on December 17, 2018.